Agile Software Architecture : Aligning Agile Processes and Software Architectures - Ali Babar, Muhammad; Brown, Alan W., 1962-; Mistrík, Ivan (Elsevier/Morgan Kaufmann, 2014)
Focuses on principles of Agile software development and gaps in the requirements of applying architecture-centric approaches. Readers will learn how Agile and architectural cultures can co-exist and support each other according to the context.